Rancang Bangun Alat Pembuat Pupuk Otomatis Berbasis Arduino ATmega - Adif Violenta Arpa; Retno Devita; Ondara Eka Putra (Journal of Computer Scine and Information Technology, 2024)
Designed and developed an automatic organic fertilizer maker using Arduino ATmega microcontroller. This tool is designed to automate the process of making organic fertilizer which usually requires a lot of energy and time. This system is equipped with temperature, humidity, and pH sensors that function to monitor the condition of the compost material in real-time. In addition, this tool is also equipped with an automatic stirring mechanism that operates based on predetermined parameters. All sensor data is processed by Arduino ATmega, which then controls the stirring motor to ensure even mixing and optimal fermentation. The developed prototype has been tested and shows that this system can operate well, producing quality organic fertilizer with minimal human intervention. The implementation of this tool is expected to increase the efficiency of organic fertilizer production and reduce dependence on less efficient traditional methods. This innovation also has the potential to support sustainable agriculture by providing a more effective and environmentally friendly alternative in fertilizer production.